2015
DOI: 10.1093/hmg/ddv298
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inSIPA1L3cause eye defects through disruption of cell polarity and cytoskeleton organization

Abstract: Correct morphogenesis and differentiation are critical in development and maintenance of the lens, which is a classic model system for epithelial development and disease. Through germline genomic analyses in patients with lens and eye abnormalities, we discovered functional mutations in the Signal Induced Proliferation Associated 1 Like 3 (SIPA1L3) gene, which encodes a previously uncharacterized member of the Signal Induced Proliferation Associated 1 (SIPA1 or SPA1) family, with a role in Rap1 signalling. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 51 publications
8
37
0
Order By: Relevance
“…The mouse protein encoded by Sipa1l3 is predicted to include a Rap GTPase-activating protein (Rap-GAP) domain, a PDZ domain, and a Cterminal domain of the SPAR protein (Greenlees et al 2015). The Rap-GAP domain is specific for Rap1, which is a GTP-binding protein and suggested, like other small GTPases, to be involved in functions associated with lens development (Rao et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mouse protein encoded by Sipa1l3 is predicted to include a Rap GTPase-activating protein (Rap-GAP) domain, a PDZ domain, and a Cterminal domain of the SPAR protein (Greenlees et al 2015). The Rap-GAP domain is specific for Rap1, which is a GTP-binding protein and suggested, like other small GTPases, to be involved in functions associated with lens development (Rao et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The peptide encoded by this variant is truncated and contains the Rap-GAP and PDZ domains, but includes only a small fragment of the C-terminal domain of the SPAR protein. Recently, Greenlees et al (2015) found that dysfunction in Sipa1l3 in human, zebrafish, and mouse, affected lens and eye development. For example, a missense mutation (p.Asp148Tyr) and a balanced chromosomal translocation affecting the 5′UTR of Sipa1l3 were found in patients with congenital cataract and other eye abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the SIPA1L3 gene has also been associated with congenital human cataracts (Evers et al, 2015;Greenlees et al, 2015). SIPA1L3 is a member of the signal-induced proliferationassociated [SIPA, also known as the spine-associated rap-gap (SPAR)] proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its expression in the rodent brain, Sipa1l3 is also localized in the developing eye in humans, mice, frog and zebrafish, especially within the lens (Evers et al, 2015;Greenlees et al, 2015;Lachke et al, 2012;Rothe et al, 2016). In 2015, two groups independently showed that mutations of the human SIPA1L3 gene are related to congenital cataracts.…”
Section: Introductionmentioning
confidence: 99%